Biotin fortification to sperm preparation medium enhances the motility and longevity by reducing lipid peroxidation in cryopreserved sperm - Ranjan, Ravi; KUMAR, M; SINGH, S P; KHARCHE, S D; SINGH, M K; CHAUHAN, M S (The Indian Journal of Animal Sciences, 2022)
Biotin supplementation to the sperm cryopreservation medium appears to be beneficial in enhancing the in vitro sperm survival without affecting the fertilizing ability. Since, biotin is an essential micronutrient, it may be a safer sperm motility enhancing agent. We inferred that the fortification of 3 μM biotin significantly (P<0.05) reduced the detrimental effects of freezing stress on motility, viability, membrane integrity and acrosome integrity of buck sperm. This particular concentration also showed significant (P<0.05) improvement in protection of sperm membrane by lipid peroxidation. Therefore, biotin may be a promising and safe alternative agent to enhance the post-thaw sperm quality in an ART. However, further studies are required to elucidate the exact molecular mechanism behind biotin-induced sperm motility enhancement.